ATORVASTATIN — 20 YEARS IN THE STRUGGLE FOR LIFE - N. G. Gogolashvili (Российский кардиологический журнал, 2018)
The efficacy and safety of atorvastatin discussed for the decrease of cardiovascular complications development.